Refined exposure assessment for Allura Red AC (E 129). (13th February 2015) - ,; ,
Abstract: Following a self‐tasking request, the European Food Safety Authority (EFSA) carried out a refined exposure assessment for Allura Red AC (E 129) taking into account additional information on its use in foods. In 2009, the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) adopted a scientific opinion on the re‐evaluation of Allura Red AC (E 129) used as a food additive. In that opinion, the Panel concluded that, at the high level, under both scenarios, that is using either the maximum permitted levels (MPLs) or the reported use levels provided by industry, intake estimates for 1‐ to 10‐year old children can be above the Acceptable Daily Intake (ADI) of 7 mg/kg body weight (bw) per day. Following this conclusion, EFSA performed a refined exposure assessment for this food colour, using new usage data from industry, as well as analytical data submitted to EFSA by Member States and the EFSA Comprehensive European Food Consumption Database. Usage data from industry were provided to EFSA for six out of the 51 food categories in which Allura Red AC (E 129) is authorised as a food additive; while analytical data from Member States were provided to EFSA for 35 food categories. Using MPLs and these new data, none of the exposure estimates exceeded the ADI of 7 mg/kg bw per day in any population.